Hidup Bakti sebagai Perwujudan Spiritualitas Trinitaris dan Misi Profetik dalam Karya Kongregasi SSpS di Pulau Timor - Lusia Tael; Oktovianus Naif; Theodorus A. Silab (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
Mission constitutes a fundamental dimension of the Catholic Church’s identity, intrinsically linked to the divine mandate to participate in God’s work of salvation in the world. Within this framework, the consecrated life of the Congregation of the Missionary Sisters Servants of the Holy Spirit (SSpS) embodies a distinctive expression of Trinitarian spirituality and a prophetic missionary vocation. In the context of Timor Island, this charism is concretely manifested through ministries that directly engage with the realities of local communities. This study adopts a qualitative methodology with a literature review approach, drawing on theological sources, congregational spirituality, and the SSpS Constitution to explore the theological and practical dimensions of the sisters’ mission. The research aims to analyze how the life and apostolate of the SSpS Sisters serve as a tangible witness to the presence of the Triune God, particularly through works in education, healthcare, social services, and pastoral ministry. The findings indicate that the sisters’ mission is deeply rooted in a faith experience centered on the Most Holy Trinity, which shapes their incarnational and intercultural approach to ministry. Their service reflects a prophetic commitment to empowering marginalized communities, promoting human dignity, and fostering social transformation. Furthermore, the integration of religious vows with active engagement in societal issues illustrates a spirituality that bridges contemplation and action, grounded in both fidelity to the Gospel and responsiveness to contextual needs. In conclusion, the consecrated life of the SSpS Sisters on Timor Island stands as a visible and dynamic sign of God’s salvific and prophetic presence. Through their holistic and transformative ministries, they contribute significantly to the mission of the Church and the common good of society, embodying a vision of the “civilization of love” rooted in Trinitarian communion and expressed in concrete service to humanity.